ANALYSIS OF THE EFFECTIVENESS OF PROCESSING SEED COTTON USING RESOURCE-EFFICIENT TECHNOLOGIES (British Journal of Global Ecology and Sustainable Development, 2022)
This article talks about the efficiency of cotton processing using resource-efficient technologies, cotton processing enterprises and technological processes.